The Impact of Hybrid Fibers on Punching Shear Strength of Concrete Flat Plates Exposed to Fire - Dalaf, A. N.; Mohammed, S. D. (Engineering, Technology & Applied Science Research, 2021)
This study presents an investigation about the effect of fire flame on the punching shear strength of hybrid fiber reinforced concrete flat plates. The main considered parameters are the fiber type (steel or glass) and the burning steady-state temperatures (500 and 600°C). A total of 9 half-scale flat plate specimens of dimensions 1500mm×1500mm×100mm and 1.5% fiber volume fraction were cast and divided into 3 groups. Each group consisted of 3 specimens that were identical to those in the other groups. The specimens of the second and the third groups were subjected to fire flame influence for 1 hour and steady-state temperature of 500 and 600°C respectively. Regarding the cooling process, water sprinkling was applied directly after the burning stage to represent the sudden cooling process. Generally, the obtained results exhibited a significant increase in the punching shear capacity of the fiber-reinforced slabs as compared to the corresponding no fiber-reinforced slabs even at elevated burning temperatures 600°C. The ultimate load was increased by about 16.6, 19, and 21.5% at temperatures of 25, 500, and 600°C respectively, for steel fiber reinforced slabs and by about 13.9, 27.2, and 34.6% for slabs containing two mixed types of fibers (steel and glass), as compared with the reference specimen at the same temperatures respectively. In addition, the results indicated that fibers’ presence in concrete resulted in gradually punching failure with more ductile mode, whereas the failure was sudden with a brittle mode in the slabs that did not contain fibers.